Auditory and visual sustained attention on tasks with varied motivation and cognitive loads in children with and without ADHD. - Russell, Emily Louise (East Carolina University, 2015)
Attention Deficit Hyperactivity Disorder (ADHD) is a common condition that can make tasks difficult for the children affected, particularly in a school environment. Continuous performance tasks are one means of evaluating sustained attention in children with and without ADHD. Traditional continuous performance tasks performed without background noise have failed to separate children with ADHD from children without ADHD. It has been theorized that children with ADHD are more susceptible to the negative effects of reduced perceptual saliency, and require more motivation (feedback) than children without ADHD. The following study aimed to test the effects of varying motivation and perceptual saliency on continuous performance tasks in children with and without ADHD and in adults without ADHD. Four sustained attention tasks were created: an auditory task with varied feedback, an auditory task with varied perceptual saliency, a visual task with varied feedback, and a visual task with varied perceptual saliency. Each task required the participants to respond to a target word or picture while ignoring non-target words and pictures. Errors types (inattention, impulsivity, total errors, and reaction time) were recorded for each task, as well as changes in error rates across the testing session. Results were analyzed using a repeated measures analysis of variance (ANOVA). Overall results indicated many differences between children and adults. In tasks with varied feedback, differences were found between the two groups of children in only the conditions with no feedback and when there was a longer delay between the response and feedback. In tasks with varied perceptual saliency, significant differences were found between the groups of children in the auditory task with a -5 signal to noise ratio. Differences in performance across tasks (vigilance decrements) were found in all three groups. Overall, findings from this study were consistent with predictions that children with ADHD may need increased feedback to perform as well as peers without ADHD, and that they may have greater difficulty performing tasks with lowered perceptual saliency. This is an important consideration for ADHD management, diagnosis, and research. In addition, further research into the role of vigilance decrement in children with ADHD is warranted.
Keywords: ADHD; Attention; Audiology; Auditory processing; Attention in children; Attention deficit hyperactivity disorder; Attention Deficit Disorder with Hyperactivity--psychology; Signal-To-Noise Ratio